Novel silica-forming peptides derived from Ectocarpus siliculosus. (July 2017) - Yeo, Ki Baek; Ki, Mi-Ran; Park, Ki Sung; Pack, Seung Pil
Graphical abstract: Highlights: New silica forming peptides (SFPs) were identified from marine algae Ectocarpus siliculosus . EctP1 and EctP2 showed higher silicification activity than R5 peptide. EctP1 showed remarkable activity below pH 7. When EctP1 and EctP2 were fused to GFP, the SFP-fused GFPs have silica forming activity. Generation of silica particles by novel SFP is useful for design of organic-inorganic complex material. Abstract: A synthetic R5 peptide showed the silica precipitation activity when added to silicic acid solution under ambient conditions. However, R5 peptide showed no silica precipitation activity below pH 7, an important pH range for biological applications. Here, we reported new silica-forming peptides (SFP), named EctP1 and EctP2. They showed better silica deposition ability than the R5 peptide. Particularly, at pH 6, EctP1 showed silica deposition activity while R5 did not. EctP1, EctP2, and R5 were genetically fused to the C-terminus of green fluorescent protein (GFP). GFP-SFP fusion proteins showed silicification ability, and GFP-EctP1 fusion protein showed the capacious silicification activity at wide pH range. The GFP-EctP2 fusion proteins showed higher protein expression levels than other fusion proteins. Furthermore, silicified GFP-SFP fusion protein exhibited an organic-inorganic complex form. These results indicate that the SFP fusion system is a novel tool for immobilizing biomolecules on silica material for biological and industrial applications.